ENGINEERING LECTURERS’ PERCEPTIONS TOWARDS EFFECTIVE CONCLUSION SECTION IN ENGINEERING FINAL YEAR PROJECT PRESENTATION - Wan Shaaidi, Wan Raihan; Mohd Radzuan, Noor Raha; Fauzi, Wan Jumani (Universitas Islam Sumatera Utara (UISU), 2023)
Final year project presentation (FYPP) assessment in the engineering field aims to evaluate students’ comprehension in the principles and concepts learnt and its application in resolving problems through engineering projects.The components assessed in FYPPs include the presentation slides that comprise introduction, content and conclusion sections. Many studies have emphasised the significance of the conclusion section in project presentations; however, there has not been much research that explores the students' knowledge and practice on conclusion moves in their FYPPs from the FYPP lecturers’ perspective. Therefore, this qualitative study, through focus group interviews, explored the perceptions of 12 engineering lecturers from a private higher institution in the east coast region of Malaysia. These lecturers, who were also the students’ FYP supervisors were asked about the students’ overall performance in delivering FYPP conclusion section, the significance of the conclusion section and the challenges faced by engineering undergraduates when presenting their conclusion section. The findings indicate that the lecturers rated students' conclusion presentations as average. The findings reveal that for the lecturers, the conclusion section is significant as it is part of the FYPP assessment rubric and it reflects students’ critical thinking and problem solving skills. In addition, the key challenges faced by students in presenting an effective conclusion section were the English language barriers and obliviousness of the essential elements of a conclusion section. Pedagogical implications include providing training that highlights the importance of the conclusion section in FYPPs, and all the moves necessary in the conclusion section.